SHARIA MARKETING MIX TERHADAP MINAT MENGINAP KEMBALI DI HOTEL GRASIA SEMARANG - Ratih Pratiwi; Moh. Irfan Latif (Magister Manajemen STIE Bank BPD Jateng, 2020)
Business and marketing have shifted from an intellectual (rational) level to an emotional level and finally to a spiritual market where consumers are more concerned about the compatibility of products and services with the spiritual values they believe. The purpose of this study is to find out how the impact of marketing mix application to the revisit intention at Grasia Hotel Semarang. This research an empirical research, data obtained from 100 visitors of Gracia Hotel and model being analized with PLS software analysis. The analysis shows that Shariah marketing mix has a significant influence on the revisit intention at the Grasia Semarang hotel. So when shariah marketing mix increased will affect the revisit intention increasement. Products, prices, places / channels, promotions, processes, people, physical form, patience and promises influence the revisit intention at the Grasia Semarang hotel. The existence of Sharia Hotels has become a new trend that is becoming widely known to the public, so it is important for organizations to maintain the quality of its services, facilities, prices, processes, compatibility of physical buildings with Islamic content as well as the honesty and accuracy of promises in conducting hotel accommodation services.